The Thermal and Electronic Properties of the Lateral Janus MoSSe/WSSe Heterostructure - Shen, Zhongliang; Ren, Kai; Zheng, Ruxing; Huang, Zhaoming; Cui, Zhen; Zheng, Zijun; Wang, Li (Frontiers in Materials, 2022)
Two-dimensional materials have opened up extensive applications for traditional materials. In particular, heterostructures can further create fantastic performances. In this investigation, the lateral heterostructure was constructed using Janus MoSSe and WSSe monolayers with armchair and zigzag interfaces. Performing first-principles calculations and molecular dynamics simulation method, the thermal stability and the semiconductor characteristics with the type-II band structure to separate the photogenerated charges of such Janus MoSSe/WSSe heterostructure are presented, which suggests the potential application of acting as a photocatalyst for water splitting. Importantly, the asymmetric interface of the Janus MoSSe/WSSe heterostructure can result in natural bending, which limits the heat flow transport. Smaller heat flow and the interfacial thermal resistance of the lateral MoSSe/WSSe heterostructure with a zigzag edge interface are mainly due to suppressed acoustic branches. These structural symmetry and interface-dependent properties show the future applications in photovoltaic and thermoelectric devices.